SINERGITAS ISLAM DAN BUDAYA DALAM KEARIFAN LOKAL (STUDI KASUS PADA KOMPLEK PEMAKAMAN RAJA-RAJA IMOGIRI DI DESA PANJAITAN IMOGIRI) (IAIN Kediri, 2017)
Indonesia is a country that has a diversity of religion, culture and language gives rights to its citizens to embrace religion as a faith embraced. Religion is believed and obeyed all the rules and orders by someone adherents of both ritual, as well as ties with what he believed. Indonesia consists of diverse cultures served as local wisdom inherent in society. Then, along with the entry and fused Islam as a religion is able to make local knowledge as a means of propaganda and intermediary for the achievement of success in spreading Islam. This indicates that the synergy between local knowledge and religious rituals because in practice these two things are always side by side as the expression of a civilized society. As done by the villagers of Panjaitan Imogiri located inside the cemetery of the Kings Imogiri, for local residents drained ceremony conducted kong surrounding communities considered to be a sacred ceremony contains blessings for their lives. Keywords: Islam, Culture, Local Wisdom